PATTERNS AND IMPACT OF SUBSTANCE ABUSE AMONG YOUTHS IN BUSHENYI DISTRICT, WESTERN UGANDA: A MIXED METHOD APPROACH - Umi Omar Bunu; Andrew Tamale; Bot Yakubu Sunday; Mikail Umar Isyaku (The Indonesian Journal of Public Health, 2025)
Introduction: Youth substance abuse is a rising public health concern globally. Over the past 20 years, youth substance abuse among youths aged 14-17 has risen to 71% in Kampala, Uganda. This study examines the patterns and impact of substance abuse among youths in Bushenyi District, Western Uganda. Aim: To assess patterns and impact of substance abuse among youths in Bushenyi District, Western Uganda. Methods: Quantitative data collected via structured questionnaires completed by 381 youths aged between 18 and 30 years were examined using chi-square and multivariate regression analysis. Quantitative findings were combined with thematic analysis of qualitative data gathered from focus group discussions (FGDs) and key informant interviews (KIIs). Results: Socially normalized and readily available substances through peer networks and unofficial supply chains were alcohol, marijuana, khat, and shisha. There were statistically significant correlations (p < 0.05) between substance usage and health problems.  The findings revealed that 46.7% of users experienced withdrawal symptoms, 49.8% experienced blackouts, and 74% reported mental health issues. Only 19.4% of users sought therapy.  Social repercussions included neglecting family responsibilities (32.5%), losing friendships (60.9%), and family conflict (51%).  In terms of income generation, 28.4% turned to crime to support their habits, with 39.4% citing problems at work.  Depression, parental neglect, and fighting when intoxicated were all validated as significant predictors by multivariate analysis. Conclusion: Youth substance abuse in Bushenyi District, Western Uganda, is a complex issue fueled by peer pressure, sociocultural acceptance, and a lack of proper mental health care.